TEST CONTROL IN ENGLISH LANGUAGE TRAINING - Malecka., I. (Continuing Professional Education: Theory and Practice, 2023)
The comparative analysis of the possibilities of information platforms for the creation of test time learning a foreign language. The comparison was made on the following criteria: the number of free options; the number of forms of tests; ease of use; the ability to use the Ukrainian language; possibility of automatic check and store the results; availability of options (the ability to add to the test images, video and audio files, and others.). According to these parameВипуск 4(45), 2015 СЕРІЯ: ПЕДАГОГІЧНІ НАУКИ 107 ters have been tested such information platforms: Google-FORMS, Quizlet, Proprofs, Kahoot !, ClassMarker, Plickers, Easy Test Maker. All these information platforms were not created in Ukraine, therefore, require special analysis before using them in the educational process for students of higher educational institutions. It was found that the main problem for Ukrainian users are limitations in functions; the impossibility of introducing Cyrillic fonts; limit the number of tests; complexity of registration (mandatory involvement of parents in order to confirm the registration); paid services. But also noted many positive features. In particular, the ability to use audio material and video. On the basis of the analysis carried out determined that the most convenient and most effective is the information platform «Proprofs ». Place your practical advice to teachers to build and test their applications in determining the degree of mastery of the student’s knowledge and skills from a foreign language. Note that this platform can be used as a model for the creation of an information platform in Ukraine. Subsequent research in this area will improve many of its functions and adapt to the peculiarities of Ukrainian education. This opens up opportunities for further research in this area.